2021
DOI: 10.3389/fcell.2021.782473
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Endogenous RNA Landscape in Epstein-Barr Virus Associated Nasopharyngeal Carcinoma

Abstract: Non-coding RNAs have been shown to play important regulatory roles, notably in cancer development. In this study, we investigated the role of microRNAs and circular RNAs in Nasopharyngeal Carcinoma (NPC) by constructing a circRNA-miRNA-mRNA co-expression network and performing differential expression analysis on mRNAs, miRNAs, and circRNAs. Specifically, the Epstein-Barr virus (EBV) infection has been found to be an important risk factor for NPC, and potential pathological differences may exist for EBV+ and EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…They constructed ceRNA and performed differential expression analysis, and they found CDKN1B, ZNF302, ZNF268, and other key differential genes. 14 In this study, we used microarrays to detect differential expression (DE) of circRNAs, mRNAs, and lncRNAs in nasopharyngeal carcinoma (NPC) tissues. We also performed network analyses (competitive endogenous RNA network analysis for circRNAs, mRNAs, and miRNAs, and co‐expression network analysis for lncRNAs and mRNAs) trying to infer the potential interactions of these functional RNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They constructed ceRNA and performed differential expression analysis, and they found CDKN1B, ZNF302, ZNF268, and other key differential genes. 14 In this study, we used microarrays to detect differential expression (DE) of circRNAs, mRNAs, and lncRNAs in nasopharyngeal carcinoma (NPC) tissues. We also performed network analyses (competitive endogenous RNA network analysis for circRNAs, mRNAs, and miRNAs, and co‐expression network analysis for lncRNAs and mRNAs) trying to infer the potential interactions of these functional RNAs.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Because circRNAs is a kind of singled‐stranded RNA with neither 5′‐3′ polarities nor polyadenylated tails, it is refrained from exo‐nucleolytic degradation and more stable. 14 , 15 , 16 Due to those characteristics, circRNAs are regarded as a promising biomarkers. Several supporting evidences have shown that circRNAs with miRNA response elements (MREs) competitively bind to miRNAs to regulate target genes expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to utilize the growingly available multi-omics data, several studies have constructed heterogenous networks combining various data types, such as phenotype ontology [105], clinical features, long non-coding RNA [106,107], and disease associations [108]. The most important step in the construction of heterogenous networks of different data types is the linkage between nodes of initially homogenous networks.…”
Section: Construction Of Protein-protein Interaction Networkmentioning
confidence: 99%
“…A previous study compared the gene expression changes between NPC and noncancerous human immortalized nasopharyngeal epithelial cell lines, Epstein-Barr virus + (EBV + ) compared with Epstein-Barr virus − (EBV − ) NPC cell lines, and metastatic vs. nonmetastatic patient samples, and constructed a circRNA-miRNA-mRNA ceRNA network. By ceRNA network analysis, they successfully identified the non-coding RNA axis that was closely biologically linked with NPC tumorigenesis ( 4 ). However, the role of ceRNA network in HNSC tumorigenesis is still unclear.…”
Section: Introductionmentioning
confidence: 99%